Development of non-state pension funds in the aspect of ecosystem formation as a method of optimizing the pension system of the Russian Federation - A. Savtsova; O. Patsenko; Yu. Deich (Вестник Северо-Кавказского федерального университета, 2022)
The problem of pension provision of citizens in modern conditions is one of the key issues in the development of the world economy. The experience of countries with developed economies in building a pension model shows that non-state pension funds are an integral part and complement to the state pension. In our country, despite the fact that non-state pension funds are also becoming more common, their potential is not fully used, the legal framework is not sufficiently perfect. We need a set of measures aimed at further development of non-state pension funds in the aspect of ecosystem formation, regulation by the state. The analysis of the profitability of non-state pension funds is presented, it is proved that non-state pension funds could become strategic investors in the Russian economy. It is proposed to maintain the previous retirement age, a guarantee of receiving pension savings from the state, co-financing of non-state pension contributions by the state and the employer, tax benefits, informing the population about the possibilities of NPFs, the introduction of the principles of «one-windowedness» in the activities of NPFs, the formation of targeting in the preparation of NGO plans, digital transformation of the provision of services and relationships with clients of NPFs.